Influence of comprehensive nursing interventions on quality of bowel preparation for colonoscopy in children (综合性护理干预对儿童结肠镜检查肠道准备质量的影响) - ZHAO Shuya (赵书亚); YANG Jiao (杨娇); ZHU Huiyun (朱慧云) (Journal of International Translational Medicine Limited, 2022)
Objective To investigate the effect of comprehensive nursing interventions on improvement of quality of bowel preparation for colonoscopy in children. Methods Totally 100 children undergoing colonoscopy were randomly divided into the control group and the observation group, with 50 cases in each group. The control group received routine nursing management, and the observation group was given comprehensive nursing interventions on bowel preparation before colonoscopy. The compliance with bowel preparation, qualified rate of bowel preparation, incidence of adverse reactions and satisfaction with nursing service among parents were measured and compared between observation group and control group. Results The rate of compliance with bowel preparation, qualified rate of bowel preparation and satisfaction rate among parents in the observation group were higher than those in the control group(P＜0. 05). The incidence of incidence of adverse reactions during the period of bowel preparation was lower than that in the control group, with a significant difference (P＜0. 05). Conclusion The comprehensive nursing is potentially effective to improve the children's compliance and quality of bowel preparation for colonoscopy. (目的 探讨运用综合性护理干预措施提升儿童结肠镜检查肠道准备质量的效果。方法 选取2021年1月-5月医院收治的行结肠镜检查的患儿100例为研究对象, 采用随机数字表法分为对照组和观察组, 各50例。对照组实施常规护理, 观察组在对照组基础上实施综合性护理干预。观察比较两组患儿肠道准备依从性、肠道准备合格率、不良反应发生率及患儿家属对医务人员工作满意度。结果 观察组患儿肠道准备依从率、肠道准备合格率、患儿家属满意度高于对照组, 差异有统计学意义 (P＜0. 05) 。观察组患儿肠道准备期间不良反应发生率低于对照组, 差异有统计学意义 (P＜0. 05) 。结论 儿童结肠镜检查肠道准备期间, 采取综合性护理干预可提高患儿依从性, 确保肠道准备质量和安全。)